Developing Instrument to Measure Student’s Capability for Future Work in Industry 4.0 at Vocational Education Culinary Program - Dewi, Desy Putriana; Soekopitojo, Soenar; Larasati, Aisyah; Kurniawan, Muhamad Farid; Hartanti, Era Ria Sofia (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Contradictions and levels of difficulty in the industrial era 4.0, especially culinary changes occur very quickly which requires humans to have the capability, to become individuals who have the skills to act. This study provides an assessment to measure the capabilities of vocational education students in statistics through instruments that have been designed and examine the competencies and soft skills that affect capabilities for future work in industry 4.0. The instrument was developed through mobile technology using Google Form and this research was conducted using quantitative methods and analyzed by confirmatory factor analysis. A total of 245 respondents from vocational education students in the culinary program were observed using a questionnaire that had been designed. Based on the results of the test analysis of exogenous confirmatory factors and endogenous indicators of capability (literacy, numeracy, ICT, critical and creative thinking, personal and social skills, and ethical understanding) showed significant value, while the reliability relationship with Cronbach alpha showed values> 0.06 which means significant. Based on the results of the goodness of fit test, this research model is fit which that means the mobile-based instruments that have been developed in this study are feasible to test the capabilities of students in vocational education at culinary programs